2016
DOI: 10.1680/jmacr.15.00449
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation resistance of GGBS concrete

Abstract: This study presents an analysis of a 30 000 strong data matrix derived from 227 studies originating from 35 countries since 1968. Similar to the fly ash effect, the carbonation of concrete increases with the incorporation of ground granulated blast-furnace slag (GGBS), but the rate increases as GGBS content is increased. This effect is greater for concrete designed on an equal water/cement (w/c) basis to the corresponding Portland cement (PC) concrete than on an equal strength basis. The Eurocode 2 specificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 97 publications
3
18
0
2
Order By: Relevance
“…It is important to highlight that these mixes did not have equal strength and that the rank order is likely to different when based on comparative strength rather than w/b. suggested that the carbonation resistance of GGBS concretes is lower than that of PC concretes with a similar w/b ratio, especially when the GGBS content is greater than 20% [Lye et al 2016]. However, according to several studies, concretes with 50% GGBS content have more or less the same carbonation resistance as PC concretes with a similar w/b ratio [Osborne 1992, Polder et al 2014 or similar strength grade [Bamforth 2004, Bouzoubaa andFoo 2005].…”
Section: Pcmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to highlight that these mixes did not have equal strength and that the rank order is likely to different when based on comparative strength rather than w/b. suggested that the carbonation resistance of GGBS concretes is lower than that of PC concretes with a similar w/b ratio, especially when the GGBS content is greater than 20% [Lye et al 2016]. However, according to several studies, concretes with 50% GGBS content have more or less the same carbonation resistance as PC concretes with a similar w/b ratio [Osborne 1992, Polder et al 2014 or similar strength grade [Bamforth 2004, Bouzoubaa andFoo 2005].…”
Section: Pcmentioning
confidence: 99%
“…In particular, it has been observed that 'green' concretes containing SCM, particularly where Portland cement is directly replaced, can have lower resistance to carbonation than traditional ones (e.g. [Papadakis 2000, Khunthongkeaw et al 2006, Lye et al 2015, Lye et al 2016). More recently, the positive effect of carbonation on the CO2 balance of the concrete industry has also attracted attention of researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of GGBS in high content could lead to increasing the depth of carbonation due to the reduced calcium hydroxide produced during hydration [26,27]. Therefore, in order to produce a ternary blended cement with better performance than binary blending of GGBS-OPC cement, High Calcium Fly Ash (HCFA), a waste material that is produced from the burning process in local power plants, has been used in addition to OPC and…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the standard curing described in Section 4.7 is applied on site. So far, for some cases, the durability design for carbonation led to excessive cover thickness when blended cement was used because a larger carbonation depth has been reported in concrete involving blended cement (Horiguchi et al 1994;Lye et al 2015Lye et al , 2016. The durability design for water penetration can avoid such problems, and the performance of the blended cement can thus be appropriately evaluated.…”
Section: Symbolmentioning
confidence: 99%